Hovenia dulcis Honey Suppresses Androgen‐Induced Epithelial–Mesenchymal Transition in Benign Prostatic Hyperplasia - Buyun Kim; Young‐Eun Kim; Eun‐Bin Kwon; Wei Li; Hye Jin Yang; Sung‐Joon Na; Sang Mi Han; Soon Ok Woo; Hong Min Choi; Siwon Moon; Young Soo Kim; Jang‐Gi Choi (Food Frontiers)
ABSTRACT Benign prostate hyperplasia (BPH) is characterized by abnormal prostate epithelial and stromal cell growth, which leads to bladder outlet obstruction (BOO) and lower urinary tract symptoms (LUTS). BPH pathogenesis involves key signaling pathways, including androgen/androgen receptor (AR) and transforming growth factor‐beta (TGF‐β)/Smad, which contribute to cell proliferation, transformation, and epithelial–mesenchymal transition (EMT). To date, the effect of Hovenia dulcis honey (HH) on BPH has not been reported. Herein, in vivo and in vitro BPH models were used to determine whether HH has therapeutic effects and its underlying mechanisms, if present. To evaluate the anti‐BPH effect of HH in vivo, mice were treated with testosterone propionate (TP; 10 mg/kg, s.c.), finasteride (Fi; 10 mg/kg, i.p.), or HH (600 mg/kg, p.o.) for 4 weeks. Additionally, HH in vitro efficacy was evaluated using a dihydrotestosterone (DHT)‐stimulated RWPE‐1 prostate cell model. HH significantly reduced prostate size, epithelial thickness, and markers of AR signaling (prostate‐specific antigen [PSA], proliferating cell nuclear antigen [PCNA], and DHT) as well as exhibited anti‐inflammatory effects by lowering the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase‐2 (COX‐2), interleukin‐6 (IL‐6), and tumor necrosis factor‐α (TNF‐α) and inhibited the EMT process by decreasing α‐smooth muscle actin (α‐SMA), neural cadherin (N‐cadherin), and vimentin levels while restoring epithelial cadherin (E‐cadherin) expression. These findings suggest that HH inhibits the androgen/AR and TGF‐β/Smad signaling pathways and may offer a novel therapeutic approach for BPH treatment.